2023
DOI: 10.3390/molecules28073118
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Efficacy of N-(4-methylpyridin-2-yl) Thiophene-2-Carboxamide Analogues against Extended-Spectrum-β-Lactamase Producing Clinical Strain of Escherichia coli ST 131

Abstract: Development in the fields of natural-product-derived and synthetic small molecules is in stark contrast to the ongoing demand for novel antimicrobials to treat life-threatening infections caused by extended-spectrum β-lactamase producing Escherichia coli (ESBL E. coli). Therefore, there is an interest in the antibacterial activities of synthesized N-(4-methylpyridin-2-yl) thiophene-2-carboxamides (4a–h) against ESBL-producing E. coli ST131 strains. A blood sample was obtained from a suspected septicemia patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…Additionally, in order to evaluate the efficacy of this stent, we also looked at N, O, and S heterocyclic formamides. Further, we studied the N, O , and S heterocycles carboxamides like 2-aryl-4-chlorophenyl-5-arylthiophene-2-carboxylates 43 N -(4-bromophenyl)furan-2-carboxamide, 37 N -(4-methylpyridin-2-yl) Thiophene-2-Carboxamide 4-bromo- N -(5-methyl-1H-pyrazol-3-yl)benzamide 16 , 44 to study the effectiveness of these scaffolds. The drug is effective against Staphylococcus aureus and Klebsiella pneumoniae , as well as resistant strains of Salmonella enterica, Acinetobacter baumannii, Enterobacter cloacae , and E. coli.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in order to evaluate the efficacy of this stent, we also looked at N, O, and S heterocyclic formamides. Further, we studied the N, O , and S heterocycles carboxamides like 2-aryl-4-chlorophenyl-5-arylthiophene-2-carboxylates 43 N -(4-bromophenyl)furan-2-carboxamide, 37 N -(4-methylpyridin-2-yl) Thiophene-2-Carboxamide 4-bromo- N -(5-methyl-1H-pyrazol-3-yl)benzamide 16 , 44 to study the effectiveness of these scaffolds. The drug is effective against Staphylococcus aureus and Klebsiella pneumoniae , as well as resistant strains of Salmonella enterica, Acinetobacter baumannii, Enterobacter cloacae , and E. coli.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the amides behave as a hydrophilic binding site against bacterial enzyme proteins, which may cause death or make static growth, leading to good inhibitory activity. 36 Further, we studied the N, O, and S heterocycles carboxamides like N-(4-bromophenyl)furan-2-carboxamide, 32 2-aryl-4-chlorophenyl-5-arylthiophene-2-carboxylates 34 4-bromo-N-(5-methyl-1H-pyrazol-3-yl) benzamide, 35 N-(4-methylpyridin-2-yl) Thiophene-2-Carboxamide 37 to study the effectiveness of these scaffolds and found effectiveness against different resistant strains of E. coli, A. baumannii, S. enterica, E. cloacae, S. aureus and K. pneumoniae. We found that heterocyclic carboxamides are pivotal in anti-bacterial activities.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of ESBL was established when a discernible increase in the zone of inhibition surrounding the combination disk (including clavulanate) was detected in contrast to the zone surrounding the disk containing only cephalosporin. Producers that satisfied the designated criteria were categorized as ESBL [ 18 ].…”
Section: Methodsmentioning
confidence: 99%